Wal-Mart : the store wars - Diermeier, Daniel (SAGE knowledge. Cases., 2016)
In early 2004, residents of Inglewood, California voted on a referendum that would change the city charter to allow Wal-Mart to build a supercentre on a huge, undeveloped lot in the city. Wal-Mart had put forward the measure after the city council refused to change the zoning of a plot on which it held an option to build. Numerous community and religious groups opposed Wal-Mart's entry and campaigned against the referendum. Walmart promised low-priced merchandise and jobs, but these groups were skeptical about the kinds of jobs and compensation that would be offered. This case examines the divisive issues.